Estimated Economics of Operation Mobile Screens in Dry Screening Process Production of Final Aggregates for Hot-Mix Asphalt. (2017) - Martišius, Mindaugas; Sivilevičius, Henrikas
Abstract: The last important production step in hot-mix asphalt aggregates production is a final screening (classifying) of secondary or tertiary crushed materials, which has to ensure high quality screening curves of end-products in accordance with standards and this process should run in most valuable economic way. The data of the screening machines from different 5 top manufacturers in same machine class were analysed in accordance with output, screening efficiency and owning and operation costs. This paper demonstrates to quarry managers possible correct choose of mobile screens, which ensure high production outputs and quality requirements and saves operation costs.